The Evolution of Representative Institutions: A Perspective Through the Prism of Constitutional History - Bojanić, Bojan Č. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper examines the historical development of representative institutions through a comparative constitutional lens, focusing on two major models: the English and the French. The English model is distinguished by legal continuity and gradual institutional evolution, whereas the French model is rooted in revolutionary constitutionalism and the principle of popular sovereignty. From the informal advisory body of the Norman period—the king’s retinue—through the Great Council (first convened in the 13th century), the English Parliament gradually evolved. Following the Glorious Revolution of 1688, it emerged as the institution that asserted supremacy over the monarch. The doctrine of parliamentary sovereignty has remained a cornerstone of English constitutional law for centuries. In France, assemblies with a dual ecclesiastical and secular character—often referred to as “synodal diets”—can be traced back to the 9th century and continued into the 13th century. The Estates-General were abolished in 1614, a fate shared by similar representative bodies across Europe, with the notable exception of Poland. A brief revival of estate representation occurred in 1789, when the Estates-General were convened once more, marking the beginning of the major political and social transformation known as the French Revolution. On June 17, 1789, the Third Estate proclaimed itself the National Assembly, thus dissolving the Estates-General and initiating a new constitutional order. The subsequent development of France’s constitutional system was extremely turbulent. The study also considers other European experiences, including those of Spain, Germany, and Italy, thereby enriching the comparative framework. Methodologically, the research combines historical analysis, comparative constitutional inquiry, and normative legal interpretation. Primary and secondary sources include constitutional texts, scholarly literature, and jurisprudential commentaries. The conclusion emphasizes that representative institutions are not merely legal constructs but also cultural and political embodiments of legitimacy and authority. Their effectiveness depends not only on constitutional design but also on democratic practice, political accountability, and civic participation.